Watermelon wilt disease: causes, harms, and control measures - Tong, Yaoyao; Du, Haosheng; Xiao, Jie; Zhou, Buchan; Zheng, Xiaojun; Deng, Yangwu; Zheng, Xianqing; Chen, Ming (Frontiers in Microbiology, 2025)
Watermelon (Citrullus lanatus L.), a globally significant economic crop generating billions of dollars annually, faces severe production limitations due to persistent Fusarium wilt caused by continuous cropping. The disease emerges following watermelon cultivation, driven by the invasion of Fusarium oxysporum f. sp. niveum, the accumulation of allelochemicals in the rhizosphere, changes in soil properties, and disruptions to the soil microbial community. These factors interact complexly, influencing plant health and soil conditions. This review examines the causes and impacts of watermelon Fusarium wilt. It explores various control strategies, including developing resistant cultivars, adjusting planting systems and agricultural practices, soil fumigation, microbial inoculants, targeted fertilization, and reductive soil disinfection. Additionally, Future wilt control may leverage nanomaterial delivery systems for precisely targeted, environmentally sustainable fungicide applications in watermelon production. This review aims to establish a scientific foundation for preventing and controlling watermelon Fusarium wilt.